Determination of the Kinetic Parameters of a Time-Temperature Integrator for the Flash Pasteurization - Dammann, Anna; Schwarzer, Knut; Vullriede, Torsten; Müller, Ulrich; Schneider, Jan (BrewingScience, 2012)
Processes for the thermal preservation of beverages in heat exchangers demand for validation methods, especially as performance qualification of a new plant. Particularly in the combination with aseptic filling systems reliable and precise tests are important. A chemical Time-Temperature Integrator (TTI) is expected to measure more accurate, cheaper and faster than conventional microbiological count reduction tests. The acidic hydrolysis of sucrose was investigated as a TTI. For the practical application the calibration of the chemical reaction is necessary in order to find the suitable parameters in terms of the acid and sucrose concentration. For the calibration of the TTI two methods were tested, the isothermal (two steps) and the non-isothermal (one-step) method. The latter revealed as more precise, thus it was used to explore the required kinetic parameters of the reaction. To cover the temperature range from 50 to 78 ?C, exemplary for the application of beer pasteurization a sugar concentration of 5 % and acid concentrations between 0.02 and 0.75?mol/L were used. With respect to products with high viscosities such as beverage concentrates a 52 % sugar syrup was used. Here the reaction is faster than with 5 % sugar. According to earlier findings the activation energies of 105.09 ? 1.07 kJ/mol (5 %) and 113.56 ? 0.83?kJ/mol (52 % sucrose) respectively were found. Of deciding importance for the application as TTI is the precise determination of the frequency factor k0 in dependency on the acid concentration. In case of both sugar concentrations a quasi-linear equation describes this correlation with high precision (R2?≥?0.998). Herewith earlier indistinct publications could be clarified. With the activation energy and the frequency factor the reaction rate can adjusted by changing the H+ concentration to different pasteurization intensities as appearing in practice. Because the activation energy of the thermal death of microorganisms is known to be about twice as high as of the TTI only largely, isothermal reactions can be converted in a direct manner. In non-isothermal cases the TTI slightly underestimates the death rate of microorganisms. The transfer of these findings into the practical scale and their verification shall be the subject of upcoming work.